Stable Isotope Records from Mount Logan, Eclipse Ice Cores and Nearby Jellybean Lake. Water Cycle of the North Pacific Over 2000 Years and Over Five Vertical Kilometres: Sudden Shifts and Tropical Connections - Fisher, D.; Wake, C.; Kreutz, K.; Yalcin, K.; Steig, E.; Mayewski, P.; Anderson, L.; Zheng, J.; Rupper, S.; Zdanowicz, C.; Demuth, M.; Waszkiewicz, M.; et al. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThree ice cores recovered on or near Mount Logan, together with a nearby lake record (Jellybean Lake), cover variously 500 to 30 000 years. This suite of records offers a unique view of the lapse rate in stable isotopes from the lower to upper troposphere. The region is climatologically important, being beside the Cordilleran pinning-point of the Rossby Wave system and the Aleutian Low. Comparison of stable isotope series over the last 2000 years and model simulations suggest sudden and persistent shifts between modern (mixed) and zonal flow regimes of water vapour transport to the Pacific Northwest. The last such shift was in A.D. 1840. Model simulations for modern and “pure” zonal flow suggest that these shifts are consistent regime changes between these flow types, with predominantly zonal flow prior to ca. A.D. 1840 and modern thereafter. The 5.4 and 0.8 km asl records show a shift at A.D. 1840 and another at A.D. 800. It is speculated that the A.D. 1840 regime shift coincided with the end of the Little Ice Age and the A.D. 800 shift with the beginning of the European Medieval Warm Period. The shifts are very abrupt, taking only a few years at most.